A new approach to enhance the reclaimed asphalt pavement features: role of maltene as a rejuvenator - Putra Jaya, Ramadhansyah; Zaid Hazim, Al-Saffar; Haryati, Yaacob; Saleem, Mhmood Khleel; Mohd Khairul Idham, Mohd Satar; Bilema, Munder; Choy, Jau Lai; Mohd Zul Hanif, Mahmud (Taylor & Francis Group, 2021)
The properties of aged asphalt can be renewed using rejuvenating agents. Rejuvenators can improve the performance of reclaimed asphalt pavement (RAP) by reducing the asphaltene-to-maltene ratio back to their initial state. This study assessed the function of maltene as a rejuvenator to renew aged asphalt. Penetration, softening point, ductility and viscosity tests were performed to determine the ideal maltene content to be incorporated into RAP. The rejuvenated asphalt samples were evaluated using rolling thin film oven (RTFO), dynamic shear rheometer (DSR), bending beam rheometer (BBR), Fourier transform infrared (FTIR), thermogravimetric (TGA) and atomic force microscopy (AFM) measurements. The outcomes were compared with virgin and aged asphalts. Both oxygenated groups and asphaltene content decreased by adding 12% maltene. Essentially, DSR, BBR, TGA, and AFM analyses divulged the comparable performance of rejuvenated asphalt with virgin asphalt, signifying the potency of maltene for practical applications.